Internal Controls to Curb Corruption in the Police Department: Challenges and Way Forward - Aslam, Muhammad Kashif (Journal of Pakistan Administration, 2022)
In the developing countries like Pakistan the expectations from the systems are democratic but the basic structures are colonial. Historically speaking, the police act of 1861 did not provide much scope to police accountability that is later altered and amended in Article (8) of The Police Order 2002 (PO) that has put in place system of police accountability based on public participation and community input. Article 155 of PO 2002 explains the penalty for certain types of misconduct. According to the Transparency International Corruption Perception Index 2020 Pakistan is at 124th number out of 180 countries. Keeping in view these statistics the importance to study the reasons of corruption in police become imperative. In Pakistan where religious intolerance, sectarian, ethnic, and gender-based violence is on the rise and on the other hand there is stagnant economic growth coupled with high rates of inflation, unemployment, poverty, and income inequality, under such situations if the law enforcement department of the country itself face the challenges like corruption and lack of integrity, then there is a need of researches and policy makers to provide direction and dimension to the stakeholders. This research aims to identify the gaps in internal controls in police department due to which image of image is being affected. It will also analyze the existing accountability mechanism in Punjab Police and the results achieved so far. It will also compare it with the internal controls of countries having best practices of the world and will also suggest policy recommendations to improve internal controls and increasing efficiency of accountability mechanism of Punjab Police.